2018
DOI: 10.1155/2018/4651218
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Agonist Corrects Defective Mini-Puberty in Boys with Cryptorchidism: A Prospective Randomized Study

Abstract: Introduction This prospective study investigated the efficacy of a gonadotropin-releasing hormone agonist (LH-RHa) in restoring defective mini-puberty. Materials and Methods Boys with isolated bilateral cryptorchidism and defective mini-puberty were randomly divided into two groups. The “surgery only” group underwent a second orchidopexy without hormonal treatment (control). The “LH-RHa” group received LH-RHa therapy followed by a second orchidopexy. The number of Ad spermatogonia and the total germ cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…The mean number of germ cells per tubule in the group treated with GnRH before surgery was significantly greater (0.88 ± 0.31) than in the group without hormonal stimulation (0.49 ± 0.52; p = 0.02). Zivkovic et al ( 28 ) also found that hormonal therapy (Buserelin ® ) improved the histopathology of the abnormal contralateral descended testis in unilateral cryptorchidism without harming the germ cells.” Vincel et al ( 29 ) presented recently a randomized study of 10 boys 8 months to 5 years old. Boys with high infertility risk (no Ad-S in the testicular biopsy) were randomly divided into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of germ cells per tubule in the group treated with GnRH before surgery was significantly greater (0.88 ± 0.31) than in the group without hormonal stimulation (0.49 ± 0.52; p = 0.02). Zivkovic et al ( 28 ) also found that hormonal therapy (Buserelin ® ) improved the histopathology of the abnormal contralateral descended testis in unilateral cryptorchidism without harming the germ cells.” Vincel et al ( 29 ) presented recently a randomized study of 10 boys 8 months to 5 years old. Boys with high infertility risk (no Ad-S in the testicular biopsy) were randomly divided into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The first study included 15 biopsies of 15 patients (7 unilateral and 8 bilateral undescended testes), which were selected prior to randomization and based on histological results. Seven patients were grouped into the High Infertility Risk group lacking Ad spermatogonia (HIR/Ad−), and 8 patients were grouped into the Low Infertility Risk group presenting Ad spermatogonia (LIR/Ad+) [ 9 , 28 , 29 ]. From randomized study, in which Ad-bilateral cryptorchid boys were treated with GnRHa (Buserelin) after the first orchidopexy (surgery), data was retrieved from 4 patients.…”
Section: Methodsmentioning
confidence: 99%
“…From randomized study, in which Ad-bilateral cryptorchid boys were treated with GnRHa (Buserelin) after the first orchidopexy (surgery), data was retrieved from 4 patients. Initial biopsies of these four patients revealed no Ad spermatogonia, indicating defective mini-puberty (Ad-group) [ 29 ]. The second testis was managed by orchidopexy and biopsied 6 months after the initial surgery and GnRHa treatment [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, in a small study of 10 boys, GnRH agonist therapy with orchiopexy improved impaired minipuberty and spermatogonia in patients with bilateral undescended testes. 46) According to international guidelines, routine hormonal therapy with hCG or GnRH/LHRH for undescended testes. is not recom mended due to the lack of evidence as previously described (Table 4).…”
Section: Hormonal Therapymentioning
confidence: 99%